A study on secondary school students’ perceptions of their motivation and attitude towards learning the english literature component - Awang, Zubaidah; Adi Kasuma, Shaidatul Akma (2010)
This study was carried out to investigate the secondary school students’ perceptions of their motivations and attitudes towards the learning of English literature component of the KBSM syllabus. A total of sixty female Form Four students were selected based on convenient sampling as the respondents of the study. A set of questionnaire was designed to gain primary data from the respondents on their motivations and attitudes towards the learning of English literature component. The overall findings of the study indicates that the students are highly instrumentally oriented and intrinsically motivated to learn the English literature component although they do possess some extent of integrative orientation as well as low level of extrinsic motivation. Apart from that, the findings also show that the students possess quite favourable attitudes towards learning the English literature component. They are willing to take necessary actions to ensure their success in learning literature as well as acquiring the language. In conclusion, some recommendations have been made to further increase students’ motivations and attitudes towards learning the English literature component and recommendations for future research have also been included in the final part of the report.